Um estudo sobre testes automatizados em aplicações React.js - Maye, Marcelina Maye Abaga (Universidade Federal de São Carlos, 2025)
Ensuring quality, performance, reducing time and avoiding rework in manually correcting code snippets are some of the requirements of developing modern web applications. Therefore, implementing automated tests is the best option in terms of efficiency, reducing project costs and improving productivity. Given the widespread use of the React.js framework, a JavaScript library for building user interfaces, it is important to obtain evidence on how these applications include automated tests. Therefore, this study focuses on exploring test automation resources in web applications that use React.js for Front-End development. To this end, the React.js library and the test automation tools it uses were studied. First, 20 open source React.js projects that implement automated tests were selected for analysis according to the established criteria. Then, the projects were cloned from GitHub and the tests were run. A table was also constructed that collects the following data: number of stars per commit, date of the last commit, test frameworks, programming language, number of tests, test LoC, production LoC, test structure, and coverage report number of stars. Based on this data obtained, the defined research questions were answered. Finally, the results indicate that among the test frameworks, React Testing Library and Jest stand out. The most used programming language was JavaScript, and the test LoC in relation to the production LoC and the number of tests in relation to the production LoC were also discussed. The results show that out of a total of 20 projects, 5 had a higher proportion of test LoC in relation to the production LoC and 7 had a higher number of tests in relation to the production LoC.
A study on automated tests in React.js applications
Keywords: Testes automatizados; React.js; React testing library; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO